Unearthing the Role of Cultural Perception in Homeownership Behavior : A Conceptual Exploration - Mulyadi, Mulyadi; Nur Zaimah, Ubaidillah (Ural Federal University, 2024)
Homeownership, viewed as a form of economic behavior, warrants a comprehensive examination considering individual perspectives. This study seeks to redefine cultural perception as an additional variable that extends the influential Theory of Planned Behavior, which serves as the foundational framework for studies in economic behavior. It presents a conceptual framework introducing the pivotal concept of cultural perception in the analysis of homeownership, drawn from an extensive literature review in economics and housing. The study delves into the notions of cultural dimensions, norms rooted in culture, homeownership, Theory of Reasoned Action (TRA), and Theory of Planned Behavior (TPB), addressing the existing gap regarding the “cultural influence” within the TPB framework. Furthermore, this study introduces a novel perspective by expanding TPB by incorporating perception variables linked to cultural values, forming a synthesis of economics, cultural, and psychological disciplines. A metric for assessing perception concerning cultural values is also proposed to effectively encapsulate the essence of the homeownership concept. This study is anticipated to augment the precision and comprehensiveness of investigations into the dynamics of homeownership behavior, and thus enrich the behavioral literature by integrating ideas from diverse disciplines.